2020
DOI: 10.3389/fpsyg.2020.01400
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership and Employees’ Thriving at Work: The Mediating Roles of Challenge-Hindrance Stressors

Abstract: Based on previous research, the conceptual model presenting the interaction between transformational leadership, challenge-hindrance stressors and thriving at work was constructed and used to generate the hypotheses for the study. Data were obtained from 542 questionnaires distributed across different organizations. The participants included ordinary employees, grassroots middle and senior managers from China. The major findings are as follows. First, transformational leadership directly is positively related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 66 publications
2
50
0
Order By: Relevance
“…The above views are consistent with the findings of Lin et al (2020) , showing that different types of stressors play different mediating roles between transformational leadership and employees’ thriving at work. We therefore suggest the following hypothesis:…”
Section: Literature Review and Research Hypothesissupporting
confidence: 89%
See 2 more Smart Citations
“…The above views are consistent with the findings of Lin et al (2020) , showing that different types of stressors play different mediating roles between transformational leadership and employees’ thriving at work. We therefore suggest the following hypothesis:…”
Section: Literature Review and Research Hypothesissupporting
confidence: 89%
“…Control variables. In order to determine the potential impact of other explanations on the empirical results, after a thorough review of the empirical studies on thriving at work, we chose age, gender and education level as control variables, which were also adopted by many scholars with thriving or stressors research ( Li et al, 2019 ; Abid et al, 2020 ; Lin et al, 2020 ). Firstly, age is crucial to thriving, since elder people are more likely to be tired at work and unwilling to learn new knowledge ( Kanfer and Ackerman, 2004 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sample item includes “At work, I find myself learning often.” Response options ranged from 1 (strongly disagree) to 7 (strongly agree). Furthermore, according to previous empirical studies on thriving at work, although it has two dimensions, scholars usually calculate the average score for subsequent analysis ( Hildenbrand et al, 2018 ; Lin et al, 2020 ). The scale’s Cronbach’s α value was 0.847 in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The second aspect attempts to construct the impact of leaders' behavior and characteristics on employees' thriving at work (e.g., Li et al, 2016;Niessen et al, 2017;Walumbwa et al, 2018). For example, it has been shown that authentic leadership (Xu et al, 2017), empowering leadership (Li et al, 2016), service leadership (Jo et al, 2020), and transformational leadership (Lin et al, 2020) are all positively related to employees' thriving. The third part of the research explores the effect of job and organizational factors (e.g., Prem et al, 2017;Jiang et al, 2020;Strecker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%